Virology and cancer biology: DNA viruses associated with transformation and tumor formation. The discovery of tumor suppressor genes - Enquist, Lynn W. (Henry Stewart Talks, 2020)
DNA viruses and transformation, Viral T antigen and cell cycle control, The linkage between Cell cycle, T antigens, Rb, E2F and p53, Transformation as an epiphenomenon of DNA viruses